4(x-1)-x=23

Simple and best practice solution for 4(x-1)-x=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-1)-x=23 equation:


Simplifying
4(x + -1) + -1x = 23

Reorder the terms:
4(-1 + x) + -1x = 23
(-1 * 4 + x * 4) + -1x = 23
(-4 + 4x) + -1x = 23

Combine like terms: 4x + -1x = 3x
-4 + 3x = 23

Solving
-4 + 3x = 23

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 3x = 23 + 4

Combine like terms: -4 + 4 = 0
0 + 3x = 23 + 4
3x = 23 + 4

Combine like terms: 23 + 4 = 27
3x = 27

Divide each side by '3'.
x = 9

Simplifying
x = 9

See similar equations:

| Y=-2x^2+4x+8 | | x+3.5x=9.90 | | -6k-7=-(6k-7) | | 10=6+2w | | 30x^3-24x^2-15x+12=0 | | 2x-84=7x-4 | | 8(p-3)=8(1+p) | | 3g-5=1 | | x-14+2x=16 | | (2y-1)(y-2)=6 | | 9x+84=12 | | 5y+13=2y+22 | | 6x-4-4x=2x-4 | | 4x+15=24 | | 24-64n=-8(-3+8n) | | 7x-13=42 | | 4x^2-17x-15=30 | | -85=5(2n-3) | | 3x+10=2x-x+18 | | 11x+25=78 | | -2(z-3)-4=18 | | -2-(12x+8)+17=3+x-(13x-4) | | -12z-29=5(z+6)-195 | | 5(v-8)-2=5v+29 | | a(t)=t^2-6t+24 | | 1.6+0.2x=0.4x-3.2 | | 60x^2+300x=0 | | 12+v=-9 | | 12x-18=53 | | (3x-x)(x+3.464)=0 | | 6m-19=-2(-3m+8) | | 3x+27=102 |

Equations solver categories